A piezo-ring-on-chip microfluidic device for simple and low-cost mass spectrometry interfacing. Issue 4 (29th January 2018) - Tsao, Chia-Wen; Lei, I-Chao; Chen, Pi-Yu; Yang, Yu-Liang
Abstract : Mass spectrometry (MS) interfacing technology provides the means for incorporating microfluidic processing with post MS analysis. Abstract : Mass spectrometry (MS) interfacing technology provides the means for incorporating microfluidic processing with post MS analysis. In this study, we propose a simple piezo-ring-on-chip microfluidic device for the controlled spraying of MALDI-MS targets. This device uses a low-cost, commercially-available ring-shaped piezoelectric acoustic atomizer (piezo-ring) directly integrated into a polydimethylsiloxane microfluidic device to spray the sample onto the MS target substrate. The piezo-ring-on-chip microfluidic device's design, fabrication, and actuation, and its pulsatile pumping effects were evaluated. The spraying performance was examined by depositing organic matrix samples onto the MS target substrate by using both an automatic linear motion motor, and manual deposition. Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) was performed to analyze the peptide samples on the MALDI target substrates. Using our technique, model peptides with 10 −6 M concentration can be successfully detected. The results also indicate that the piezo-ring-on-chip approach forms finer matrix crystals and presents better MS signal uniformity with little sample consumption compared to the conventional pipetting method.